Bangladesh's Economic Diplomacy Toward China: Implementing Vision 2041 - Md Moshrakul Alam Badhan; Saydur Rahman Nion (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Economic diplomacy is an important aspect of the international arrangements of a country. Since achieving independence in 1971, the government of Bangladesh has actively pursued economic diplomacy. An important part of Bangladesh's economic diplomacy has always been the pursuit of foreign direct investment (FDI). China is one of the major foreign direct investor country in Bangladesh. In this paper, the author tried to explore the aims of Bangladesh's economic diplomacy, the approaches of Bangladesh’s economic diplomacy toward China to implementing Vision 2041, and the challenges of Bangladesh’s economic diplomacy toward China.